Positionspapier der Deutschen Gesellschaft für Pneumologie und Beatmungsmedizin e. V. (DGP) zur elektronischen Zigarette (E-Zigarette) = Position paper of the German Respiratory Society (DGP) on electronic cigarettes(e-cigarettes) in cooperation with the following scientific societies and organisations: BVKJ, BdP, DGAUM, DGG, DGIM, DGK, DKG, DGSMP, GPP - Nowak, Dennis; Herth, Felix (Das Gesundheitswesen, 2015)
Thieme E-Books & E-Journals